A educação em saúde clientes de unidades básicas de saúde: uma contribuição do enfermeiro - Lopes, Ana Paula Riberto (1998)
This assay deals with the educational practicing in health done by the nurse with patients in Health Basic Units (HBU) in the urban area in Juiz de Fora city (MG); its aim was to analyse the educational practicing in health by drawing the nurse' s profile in the HBUs, describing the developed actions, identifying the didatic pedagogical strategies used during the educational practicing and discussing the restrictive and facilitating factors do this practicing. The subjects were the nurses of the health basic net who worked in this urban area, and data were collected through questionnaires and observation of the educational practicing. It was a descriptive research, like a job-analysis. Data were presented in tables and analysed according to the theoretical reference. The results showed that: the majority of nurses had worked for more than ten years in health units and they were specialized in Public Health; the major part hadn't had teaching formation; comprehension in health education was driven towards information, illnesses prevention and health troubles; patient's participation was regarded as extremely important in educational actions; the most applied teaching strategy was oral explanation. Among the teaching resources, the most used ones were posters and folders. The nurses had pointed out the staff support and the community acceptance as facilitating factors to the development of educational activities, and, as restrictive factors, the lacking of material, time and human resources. Measures for crew integration and human resources and material expansion were indicated by themselves as necessaries to achieving a better qualification for the educational practicing in health.